Analisis Kinerja Keuangan Berdasarkan Rasio Likuiditas Dan Rasio Solvabilitas: (Studi Kasus PT. Indocement Tunggal Prakarsa Tbk Periode 2007-2021) - Silvia Maulita; Rita Tri Yusnita; Kusuma Agdhi Rahwana (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
Financial performance is a form of achievement achieved by a company in managing finances and also describes the state of a company’s performance. This study aims to determine the simultaneous and partial effect of the Liquidity variable as measured by the Current Ratio (CR) and the Solvency variable as measured by the Debt to Equity Ratio (DER) on financial performance as measured by the Profitability Ratio (ROA). The population used in this study is the quarterly financial reports of PT. Indocement Tunggal Prakarsa Tbk 2003-2021. The method used in this research is descriptive research with a quantitative approach. Selection of the sample using purposive sampling. The sample used is the quarterly financial reports of PT. Indocement Tunggal Initiative 2007-2021. The data source in this study is secondary data in the form of audited financial reports obtained from www.idx.co.id. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the research results it is concluded that liquidity and solvency simultaneously have a significant effect on financial performance. Liquidity partially has a significant effect on financial performance. Solvability partially has a significant effect on financial performance.